Occurrence of Pesticides, Mycotoxins, and Heavy Metals in Distilled Alcoholic Beverages: A Review of Contaminants and Health Risks - Tomislav Rot; Sunčana Gavran; Jurislav Babić; Ante Lončarić (Foods)
Distilled alcoholic beverages may contain pesticides, mycotoxins, and heavy metals originating from raw materials, environmental factors and technological processes. This review paper analyses the existing regulations related to these contaminants, their impact on health and the risk assessment associated with their consumption. Sources of contamination are discussed, including the influence of climatic conditions and emerging environmental risks on the occurrence of contaminants in raw materials, as well as the transfer of all contaminants during the distillation process. Furthermore, analytical detection methods and strategic measures to reduce consumer exposure are reviewed. The results of the review highlight the need for continued research, improvement of control methods and adaptation of regulatory standards in line with new scientific knowledge.